Enhancing Knowledge and Practices for Inclusive Education: A Community Engagement Program for Early Detection and Intervention in Elementary School Students' Development - Widi Arti; Herista Novia Widanti; Tri Linggowati; Talitha Alya Hanifah; Safara Anggita (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents the outcomes of a community engagement program conducted in collaboration with SD Muhammadiyah 01 Candi Labschool UMSIDA in Sidoarjo District, Indonesia. The program aimed to enhance the knowledge and practices of 22 regular teachers, 8 shadow teachers, and 3 educational staff members regarding early detection and intervention strategies for elementary school children, particularly those with special needs. The program, led by the Department of Physiotherapy and Primary School Teacher Education at Muhammadiyah University Sidoarjo, utilized a two-way lecture method, demonstrations with visual media, and mentorship in creating visually-based learning models. The program successfully increased the participants' understanding of stimulation, early detection, and the importance of attention to the learning needs of children with special needs through visual-based learning models. The evaluation of the program's effectiveness and satisfaction levels was conducted throughout its implementation, with the opportunity to modify methods if deemed ineffective. The implications of this community engagement initiative are relevant to professionals and researchers in the field of inclusive education worldwide, providing valuable insights for enhancing educational practices and fostering the development of diverse learners in elementary school settings. Highlight: Early detection for timely intervention Enhancing teacher knowledge in inclusive education Visual-based learning for special needs student Keyword: Early Detection, Inclusive Education, Teacher Knowledge, Visual-Based Learning, Special Needs